Comparative ecological traits and environmental responses of two distinct populations of the critically endangered Cycas fairylakea in Guangdong, China - Liang, Dan; Wei, Yimin; Wang, Peng’ao; Liu, Xiuting; Wang, Penghuan; Liu, Yaojun; Zeng, Siyuan; Wang, Ruijiang (Frontiers in Ecology and Evolution, 2024)
Cycas fairylakea is an endemic and Level-One National Key Protected Wild Plant in China. It is distributed in the Meilin Reservoir and Tanglangshan Country Park in Shenzhen. This study investigated two newly discovered wild populations in Taishan and Yangjiang, Guangdong Province. The forest community characteristics and population structure of these newly discovered populations remain unknown, and the sex ratio as well as the species’ responses to environmental factors have never been reported, despite their importance for the in-situ conservation of this Cycad. We conducted a comprehensive investigation of the ecological traits (soil properties, community characteristics, and phylogenetic diversity) and population characters (size, age structure, sex ratio, and spatial pattern) of C. fairylakea and determined the impact of environmental factors on the age structure and sex ratio. The results showed that the species number and composition of the two communities differed, yet no significant differences were observed in the plant diversity indices, with close phylogenetic affinities among species. Moreover, the sex ratio, determined by the MADS-Y marker, was relatively balanced. The age structure of the two populations exhibited a “reverse-J” shape, and the survival curves were of the Deevey’s type III, indicating low natural regeneration capacities with high mortality in the early stage. Redundancy analysis identified the soil properties as constraining factors of the C. fairylakea sex ratio, while climate factors and community species diversity and evenness indices positively impacted the sex ratio. The combined effects of soil, climate, topography, and shrub layer plant diversity were the main factors influencing the age structure and sex ratio of the C. fairylakea populations. A balanced sex ratio ensures reproductive capacity, which maintains population stability. However, the structural and numerical characteristics of C. fairylakea in the two regions are constrained by environmental pressures. The implementation of well-considered artificial conservation strategies and the safeguarding of the habitat are intended to bolster the survival rate of the seedlings, promote the healthy growth of middle-aged individuals, and maintain the sustained stability of the natural population of C. fairylakea.